The assessment of river water quality in Kuantan - Norhasmira Idayu, Harun (2019)
Assessing water quality is of crucial importance to both society and the environment. Deterioration in water quality induces substantial risk to the living ecosystem and can have detrimental effects on the local economy. Therefore continuous water monitoring with appropriate treatment and management approach is necessary. Thus, the current study focuses on the assessment of river water quality in Kuantan River basin. It involved Galing, Belat and Kuantan rivers that link to each other. Understanding the relationship of inorganic ions and selected parameters are important and one of the improvements for river water management. Thus, the research focuses on understanding the distribution of inorganic ions concentrations and its relationship with selected water quality parameters subsequently classification of the monitored rivers was made based on the National Water Quality Standards (NWQS). The detail monitoring was done to the most polluted river among the study area. The ion chromatographic systems were used for analyzing the behavior of inorganic ions. The HCO3- ion concentration was determined using Ion Exclusion Chromatography. Meanwhile, SO42-, Cl-, NO3-, Na+, NH4+, K+, Mg2+, Ca2+ ions were identified by Ion-Exclusion Chromatography/CationExchange Chromatography. The statistical analysis was made by using ANOVA. The classification was made based on the NWQS indicates that the Galing River is the most polluted river in the study area. Thus, detail monitoring on Galing River is done and from the obtained results, the concentration of Cl- and Na+, is high due to the environmental burden and anthropogenic influence that was detected in G2 compared to the rest of the Galing River area. In terms of total nitrogen (TN), chemical oxygen demand (COD), and dissolved oxygen (DO), the western side of the Galing River was affected by higher human activity such as wastewater from industrial, household, and agricultural, which classify within higher class compared to the eastern side. Class V or near Class V for pH values were obtained at upstream on the western side of the Galing River (G1a-1 and G1a-2) in the industrial area. In general, the study provides the current status of river water quality on Kuantan river basin. On top of that, the application of ion exclusion chromatography can be used as the reference for other environmental researcher and related institutional bodies in water monitoring process.